Pemeriksaan Antigen Spesifik Prostat (PSA) untuk Deteksi Dini Kanker Prostat: Analisis Berbasis Bukti: Tinjauan Pustaka - Saptia Nugraha, Ilham; Trisnanto, Agung (PT Kalbe Farma Tbk., 2026)
Introduction: Prostate-specific antigen (PSA) screening has transformed the early detection of prostate cancer, yet its widespread implementation remains controversial due to concerns over overdiagnosis, overtreatment, and questionable mortality benefit. This article evaluates the contemporary evidence regarding the benefits and harms of PSA-based screening, synthesizing findings from major clinical trials, cost-effectiveness analyses, and international guidelines. Methods: An evidence-based analysis using data from pivotal trials such as ERSPC, along with recent meta-analyses, biomarker advancements, MRI-based protocols, and national screening guidelines from the USPSTF, EAU, NCCN, and others. Results: PSA screening may reduce prostate cancer-specific mortality, particularly in men aged 55–69 years. It facilitates early detection, enhances access to curative therapies, and promotes broader health engagement. However, it carries significant risks, including overdiagnosis of indolent tumors, overtreatment-related morbidity, false positives, psychological distress, and economic burden. Mortality outcomes across studies remain inconsistent, prompting a shift toward personalized, risk-adapted screening guided by age, comorbidities, family history, biomarkers (e.g., PHI, 4Kscore), and multiparametric MRI. Conclusion: PSA screening should not be universally applied but rather employed through shared decision-making and individualized risk assessment. Continued research is warranted to optimize outcomes and inform equitable screening policies, particularly in resource-limited settings.